Evaluation of long-term power capture performance of a bistable point absorber wave energy converter in South China Sea. (1st October 2021) - Zhang, Nianfan; Zhang, Xiantao; Xiao, Longfei; Wei, Handi; Chen, Weixing
Abstract: Nowadays, extensive research has been conducted to generate electricity from ocean waves, but there are not too many studies on the capture of wave energy in a specific ocean area. As the largest sea area in China's offshore waters, the South China Sea contains a large amount of wave energy and is regarded as a natural wave energy power plant. A comparative study was conducted to investigate the effects of wave energy converter (WEC) parameters on the long-term power capture performance of a bistable point absorber WEC installed in the South China Sea in this paper. Combined with the joint probability distribution of significant wave height H s and peak wave period T p in South China Sea, a mathematical model was developed for the evaluation of long-term power performance of WECs. The governing equations of the point absorber WEC were established using the hybrid frequency-time domain method. The dynamic response and captured power can be obtained after numerically solving the equations of motion with the 4th order Runge-Kutta Method. The results show that the bistable mechanism has great advantages in the long-term captured power of WEC. In general, a circular truncated cone-shaped buoy WEC with a larger buoy size and smaller nonlinear parameter tend to result in better long-term power capture performance. The insights given in this study provide a motivation and foundation for developing a complete set of performance optimization methods of point absorber WECs installed in South China Sea. Highlights: A mathematical model was developed for evaluation of long-term power performance of a point absorber WEC (PAWEC). The long-term power performance of the WECs with and without bistable mechanism was numerically simulated. The advantages of the bistable mechanism in the long-term captured power of WEC were confirmed. The effects of WEC parameters on the long-term performance of the PAWEC were clarified.